Ultimate weird but true 3. (Washington, D.C. : National Geographic, 2015)
Presents facts, brief stories, photos, and illustrations showing that fact can be as weird as fiction.
Ultimate extremes -- Larger than life -- Take a number -- Wacky world -- Strange smarts -- Speed demons -- That's gross! -- Reallly wild! -- Eyepoppers.
Includes index.
8-12
3-7
Keywords: Curiosities and wonders -- Juvenile literature; Curiosities and wonders; Curiosities and wonders; JUVENILE NONFICTION / Curiosities & Wonders; JUVENILE NONFICTION / Reference / Almanacs; JUVENILE NONFICTION / Science & Nature; Juvenile works